Insights into arsenic multi-operons expression and resistance mechanisms in Rhodopseudomonas palustris CGA009 - Zhao, Chungui; Zhang, Yi; Chan, Zhuhua; Chen, Shicheng; Yang, Suping (Frontiers in Microbiology, 2015)
Arsenic (As) is widespread in the environment and causes numerous health problems. Rhodopseudomonas palustris has been regarded as a good model organism for studying arsenic detoxification since it was first demonstrated to methylate environmental arsenic by conversion to soluble or gaseous methylated species. However, the detailed arsenic resistance mechanisms remain unknown though there are at least three arsenic-resistance operons (ars1, ars2 and ars3) in R. palustris. In this study, we investigated how arsenic multi-operons contributed to arsenic detoxification in R. palustris. The expression of ars2 or ars3 operons increased with increasing environmental arsenite (As(III)) concentrations (up to 1.0 mM) while transcript of ars1 operon was not detected in the middle log-phase (55 h). ars2 operon was actively expressed even at the low concentration of As(III) (0.01 μM), whereas the ars3 operon was expressed at 1.0 µM of As(III), indicating that there was a differential regulation mechanism for the three arsenic operons. Furthermore, ars2 and ars3 operons were maximally transcribed in the early log-phase where ars2 operon was 5.4-fold higher than that of ars3 operon. A low level of ars1 transcript was only detected at 43 h (early log-phase). Arsenic speciation analysis demonstrated that R. palustris could reduce As(V) to As(III).